(untitled) (Pakistan Journal of Science, 2022)
In this study, the authors mostly deal with the issues of handing out different kinds of sewage created by tanneries productions with particular emphasis to chrome tanned sewage,H2S/NH3 emission handling and water conservation at cooling tower. The agents that creates this waste as a potentially harmful is hexa and trivalent chromium, black killer gas (H2S) and wastage of water blow- down at cooling tower, the authors show the hazards of unexpected all above three issues and in this contribution, a new retrofit methods of handling tannery waste water, contamination air emission. Tannery dirty water includes a great quantity of chemical mixture containing materials so the efforts were made to categorize physiochemical factor of tannery dirty water and biological treatment.